Pengaruh Belanja Modal Dan Pendapatan Asli Daerah Terhadap Pertumbuhan Kinerja Keuangan Daerah Pada Bpkad Kabupaten Pohuwato - Moh. Jamal Moodoeto (Universitas Gorontalo, 2018)
The purpose of this study was to determine how the effects of capital spending and original local revenue to growth in the area of financial kinaerja BPKAD Pohuwato. The data were obtained by downloading the data on the Directorate General of Fiscal Balance State (djpk.go.id) and on BPKAD Pohuwato. Analysis of the data in this study multiple regression using SPSS 21.These results indicate that partially and simultaneously discovered that the Capital Expenditure of the financial performance of no significant influence certainly shows that the tendency of trends in the data that are inconsistent between the Capital Expenditure Financial Performance for trends in the data for each year is different. Regional Income on financial performance is not significant area shows the negative influence because when PAD increases, financial performance will experience decline as a result of the inefficiency of budgetary revenues local government default. Capital Expenditure and revenue (PAD) simultaneously no significant effect on financial performance Pohuwato 2010-2014. These results indicate that the Capital Expenditure and revenue (PAD) was not able to give an interpretation or able to explain the variable Financial Performance. The greatest effect is seen from the determination coefficient of 12.1%. Thus the need for the Government Pohuwato conducted a study on the importance of public goods expenditures or development expenditures to increase revenues Pohuwato